A comparative study on epoxy based composites filled with pineapple/areca/ramie hybridized with industrial tea leaf wastes/GFRP. (2020) - Gokulkumar, S.; Thyla, P.R.; Prabhu, L.; Sathish, S.; Karthi, N.
Abstract: Human beings have been strongly aware of environmental degradation, noise pollution and its human health implications as a result of the unprecedented use of synthetic fibres. The search is to develop a new class of material using eco-friendly fibers extracted from the environmental and industrial wastage which is to be better alternative for existing green composites. In this work, an industrial tea waste has been considered as filler materials due to its excellent sound absorbing properties. In addition to achieve a comprehensive characterization, sound absorbing properties are also to be potentially tested. In this context, three combinations of three different natural fibers (pineapple, areca and ramie) are hybridized with waste tea (powder form) and GFRP were fabricated by a compression molding process with the combinations of 40% reinforcement and 60% epoxy matrix material in a constant proportion. A hydrophilic content present in natural fibers are transformed to hydrophobic by 5% of alkyl treatment for enhancement of bonding between fiber and matrix phase. Mechanical, chemical, morphological, acoustical, humidity absorption and chemical examinations are done for laminates fabricated. The results are evaluated and compared to establish the possibility of using it as a new material for engineering applications especially in under-floor protection, engine decorative cover for passenger cars, wheel housing and inner door panel in automobiles.